Large spin accumulation and crystallographic dependence of spin transport in single crystal gallium nitride nanowires - Tae-Eon Park (Nature Portfolio, 2017)
Semiconductors are promising for high performance spintronics but the low functioning temperature hampers their applications. Here the authors achieve a strong room temperature modulation of spin-dependent resistance in GaN nanowires, which marks an important step towards practical spintronic devices.